PENGARUH GAYA HIDUP DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPATU PRIA DI KABUPATEN MOJOKERTO - YUNITA (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: The main functionof shoesisasprotectorof our feetin walking. However, as the developmentof humancivilization, nowthe shoehasmore functionsthan justthat.This studyfocused on theconsumeroutletAl-Farisi becausethisoutletshoeshaveadvantagesofthe modelarealwayschangedeverytwoweeks.This studyaimstodiscussandanalyzeInfluence of Lifestyle and Price onPurchasing Decisionsin Men’s ShoesinMojokerto(Studies inConsumerOutletAl-Farisi Pusat Perkulakan Sepatu Trowulan).This study used acausalapproach. The population inthis studywasAl-Farisi Outletconsumerswhopurchaseanduse theshoes. Samples are taken of104peoplewithaccidental sampling technique. Measuring instrument usedwas aquestionnaire, andthe datawere analyzedwithmultiple linear regression. The results showedthat partiallifestyleandpriceaffectpurchasing decisions. The results showedthat simultanlifestyleandpriceaffectpurchasing decisions. Keywords:lifestyle, price, purchasing decisions.